Amish Marketplace : The Coffee Corner - Book 3 - Clipston, Amy; Clipston, Amy. (Grand Rapids, Michigan : Zondervan, 2020)
"In this third installment of Amy Clipston's Amish Marketplace series, an acquaintance grows into love over a few well-timed cups of coffee"--
Keywords: Amish -- Fiction; Bakers -- Fiction; Coffee shops -- Fiction; Farmers' markets -- Fiction; Man-woman relationships -- Fiction; Grief -- Fiction; Bird-in-Hand (Pa.) -- Fiction; Romance fiction; Religious fiction; Christian fiction